Study of Cultural Structure and Values in Legend Orang Kayo Hitam and Its Utilization as an Alternative Teaching Material for Fictional Prose Studies - Liza Septa Wilyanti; Sovia Wulandari (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
This research was conducted to describe the structure and cultural values contained in the legend of the Orang Kayo Hitam, as well as to find appropriate forms of teaching materials for Fictional Prose Studies courses. The research method used in this study is the ethnographic method. Data collection techniques in the form of interviews, field notes, and documentation. The results of the study found that the legend of the Orang Kayo Hitam has four story fragments, namely the story OKH: Sang Pemberani, OKH: Genealogy, OKH: Si Ginjai Keris Sang Raja, and the legend OKH: The Origins of the Selected Land of Jambi Country. The results of the research can be used as an alternative teaching material for lectures on Fictional Prose Studies in the form of hand outs.Keywords: legend, structure, cultural values, teaching materials